2023
DOI: 10.1159/000533443
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Triamcinolone Acetonide for Diabetic Macular Edema and Macular Edema Secondary to Retinal Vein Occlusion: A Meta-Analysis

Abstract: Background: The comparative safety and efficacy of different doses of intravitreal triamcinolone acetonide (IVTA) for diabetic macular edema (DME) and macular edema (ME) secondary to retinal vein occlusion (RVO) is unclear. Objectives: This meta-analysis aimed to compare the safety and efficacy of different doses of IVTA in this setting. Methods: A systematic literature search for randomized clinical trials (RCTs) was conducted on Cochrane Library, Ovid MEDLINE and EMBASE from January 2005 to May 2022. Studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In the literature, there are various case reports of retinal intoxications following high-dose intravitreal amphotericin B injections [ 32 , 33 ]. Furthermore, other studies showed that higher doses of intravitreal triamcinolone acetonide (IVTA) for diabetic macular edema achieved greater improvements in visual acuity and reductions in retinal thickness than lower doses [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are various case reports of retinal intoxications following high-dose intravitreal amphotericin B injections [ 32 , 33 ]. Furthermore, other studies showed that higher doses of intravitreal triamcinolone acetonide (IVTA) for diabetic macular edema achieved greater improvements in visual acuity and reductions in retinal thickness than lower doses [ 34 ].…”
Section: Discussionmentioning
confidence: 99%